2005
DOI: 10.1091/mbc.e05-01-0071
|View full text |Cite
|
Sign up to set email alerts
|

Global Roles of Ssn6 in Tup1- and Nrg1-dependent Gene Regulation in the Fungal Pathogen,Candida albicans

Abstract: In budding yeast, Tup1 and Ssn6/Cyc8 form a corepressor that regulates a large number of genes. This Tup1-Ssn6 corepressor appears to be conserved from yeast to man. In the pathogenic fungus Candida albicans, Tup1 regulates cellular morphogenesis, phenotypic switching, and metabolism, but the role of Ssn6 remains unclear. We show that there are clear differences in the morphological and invasive phenotypes of C. albicans ssn6 and tup1 mutants. Unlike Tup1, Ssn6 depletion promoted morphological events reminisce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
1
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(118 citation statements)
references
References 67 publications
5
111
1
1
Order By: Relevance
“…Therefore, it is tempting to speculate that Yak1 may modify the activity of the Tup1-Nrg1, Tup1-Rfg1, or chromatin remodeling complexes in response to hypha-inducing signals and consequently allow derepression or activation to take place. A large fraction of the genes that are hypha-induced in a Yak1-dependent manner have been shown to be repressed by Tup1 Garcia-Sanchez et al, 2005), suggesting that Yak1 may interfere with Tup1-mediated repression. This hypothesis is supported by our observation that inactivation of the TUP1 gene can bypass the Yak1 requirement for filamentation (Figure 7), suggesting that Yak1 might function as a repressor of Tup1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is tempting to speculate that Yak1 may modify the activity of the Tup1-Nrg1, Tup1-Rfg1, or chromatin remodeling complexes in response to hypha-inducing signals and consequently allow derepression or activation to take place. A large fraction of the genes that are hypha-induced in a Yak1-dependent manner have been shown to be repressed by Tup1 Garcia-Sanchez et al, 2005), suggesting that Yak1 may interfere with Tup1-mediated repression. This hypothesis is supported by our observation that inactivation of the TUP1 gene can bypass the Yak1 requirement for filamentation (Figure 7), suggesting that Yak1 might function as a repressor of Tup1.…”
Section: Discussionmentioning
confidence: 99%
“…b ϩ indicates Tup1-negative regulation as inferred from transcript profiling data available in Garcia-Sanchez et al (2005) and Kadosh and Johnson (2005 Table 3). For these latter genes, we observed that 1) the activation ratio was always lower in the mutant strain than in the wild-type strain and 2) the level of expression in wild-type yeast cells was higher than that in yeast cells of the yak1⌬/yak1⌬ mutant strain (Table 3).…”
Section: The Yak1 Kinase Is Necessary For the Up-regulation Of A Subsmentioning
confidence: 99%
“…Furthermore, NRG1 itself is downregulated during the yeast-to-hypha transition (71). Transcriptional profiling suggests that Nrg1 is also involved in the negative regulation of filament-specific transcripts but only targets Tup1 to a subset of promoters in the C. albicans genome (199,262,406,407). Nrg1 also has an important role in biofilm formation, where high levels of NRG1 inhibit yeast-tohypha morphogenesis yet still produce yeast cells that incorporate into biofilms.…”
Section: Major Morphogenetic Signaling Cascadesmentioning
confidence: 99%
“…Although transcriptional profiling reveals the conditions or transcriptional factors that regulate the expression of a protein, the function of the protein may remain unknown. For example, Rbe1p is a predicted secreted protein that is negatively regulated by Ace1p (256), Rim101p (23), Ssn6p (120), and Efg1p (356). Secreted proteins with enzymatic functions may catalyze reactions in which cell wall components are substrates, particularly glucan and chitin or other substrates, as in the case of trehalase.…”
Section: Predictionsmentioning
confidence: 99%